The fossil register of plesiosaurs (Diapsida, Sauropterygia) in Peru - Meza-Velez, Ivan (2021)
In this paper, the plesiosaur records for Peru are reviewed and material referring to plesiosauria deposited in the Natural History Museum of the UNMSM is described. The plesiosaur records of Peru are extended since the Valanginian-Hauterivian (Lower Cretaceous) to the Maastrictian (Upper Cretaceous). In relation to the taxonomic position, the material is attributable to Plesiosauria indet., Elasmosauridae indet., while the new material studied is possibly Pliosauroidea indet., and will be the first records of this group in Peru. Likewise, the Morro Solar plesiosaur is the only one from the Lower Cretaceous and the oldest in Peru.